Infrastructure of social control: A multi-level counterfactual analysis of surveillance and Black education. (November 2022) - Johnson, Odis; Jabbari, Jason
Abstract: In response to the continued reoccurrence of school shootings, policymakers have increased surveillance measures to ensure safer learning environments. However, in addition to being used to preempt school shootings, these surveillance measures may have increased the capacity of schools to identify and punish students for more common and less serious offenses, which may negatively impact the learning environment. Using counterfactual and multi-level modeling strategies with national survey data, we show that schools ranking highest in surveillance infrastructure suspend more students than schools that rank among the lowest in their surveillance capability, even when controlling for school social disorder and student misbehavior. In addition to suspending more students, the infrastructure of surveillance reduces test scores in mathematics and college enrollment altogether for suspended and non-suspended alike, suggesting the presence of negative spillover effects. We conclude that the "safety tax" students pay with their average levels of test performance and college going rates is greatest for Black students of both genders given their overrepresentation in high-surveillance schools. The article concludes with a discussion of control wave theory and the study's implications for policy and practice. Highlights: All else equal, suspension rates are higher in high versus low surveillance schools. Blacks are four times more likely to attend a high versus low surveillance school. High surveillance schools lower all students' math scores and odds of college entry. Between-school variation in math scores increases once suspensions are controlled.